Vietnam Monopoly Market: Vietnam Electricity (EVN) State-Owned Enterprise Literature Study - Sri Haryani; Henni Mande; Rukhayati (Jurnal Sinar Manajemen, 2024)
This research is an insight into the literature related to the monopoly market in Vietnam, namely the State-Owned Enterprise Vietnam Electricity (EVN). State-owned Vietnam Electric Group (EVN) is Vietnam's largest electricity company, responsible for electricity generation, transmission and distribution across the country. EVN plays an important role in ensuring stable electricity supply and expanding electricity access in both urban and rural areas. EVN's monopoly market study in Vietnam is a study related to the structure of the electricity industry in Vietnam.